Answer:
Type that out please I can't read it sideways
Step-by-step explanation:
Your answer would be 22 because it says <em>"sum"</em> which means <u>add.</u> Then it says "<em>of three consecutive <u>even</u> numbers</em>" which means you're going to be adding <u>three</u> of the <em>same <u>even</u> number </em>to get 66. 22 is an <u>even</u> number, so let's try it out: 22 + 22 + 22 = 66. (You can also divide 66 by 3.) 22 is the cOrrect answer.
Hope this helps,
♥<em>A.W.E.<u>S.W.A.N.</u></em>♥
Answer: X = y - yi - 7i
Y = (x + 7i)/(1 - i)
Step-by-step explanation: for the case of (X) you only need to pass the 7i to the other side with the subtraction sign (-7i), then we get this equation:
x + 7i = y − yi
X = y - yi - 7i
in the case of the (Y), first we select the common multiple.
y - yi = y(1 - i)
if we replace it in the original expression, we get the following equation:
x + 7i = y(1 - i)
after that you can pass the value (1 - i) to the other side dividing,
Y = (x + 7i)/(1 - i)
42 - 6 = 36 - 1
36 - 6 = 30 - 2
30 - 6 = 24 - 3
24 - 6 = 18 - 4
18 - 6 = 12 - 5
12 - 6 = 6 - 6
6 - 6 = 0 - 7
42/6 = 7